A Total of 207 Days of Veno-Venous Extracorporeal Membrane Oxygenation Support for Severe COVID-19 Prior to Successful Lung Transplantation: A Case Report - Naar, Jan; Kruger, Andreas; Vondrakova, Dagmar; Janotka, Marek; Kubele, Jan; Lischke, Robert; Kolarova, Milena; Neuzil, Petr; Ostadal, Petr (Journal of personalized medicine, 2022)
Veno-venous extracorporeal membrane oxygenation (VV-ECMO) is a life-saving treatment for respiratory failure that may serve as a bridge to patient recovery or lung transplantation. In COVID-19, recovery is somewhat unpredictable and occasionally occurs after >100 days on VV-ECMO support. Thus, determining therapy cessation may be difficult. We report the case of a 59-year-old male without specific risk factors admitted to a tertiary center for rapidly progressive respiratory failure due to severe COVID-19, despite aggressive mechanical ventilatory support. Immediate insertion of VV-ECMO was associated with prompt resolution of hypoxemia and hypercapnia; however, all therapeutic efforts to wean the patient from VV-ECMO failed. During the prolonged hospitalization on VV-ECMO, sepsis was the most life-threatening complication. The patient overcame roughly 40 superinfections, predominantly affecting the respiratory tract, and spent 183 days on antimicrobial treatment. Although the function of other organ systems was generally stable, gradually progressive right ventricular dysfunction due to precapillary pulmonary hypertension required increasing doses of inotropes. A successful lung transplantation was performed after 207 days of VV-ECMO support. The present case provides evidence for prolonged VV-ECMO therapy as a bridge to lung transplantation in severe COVID-19 despite numerous, predominantly infectious complications.
Keywords: coronavirus disease; extracorporeal membrane oxygenation; lung transplant; acute respiratory distress syndrome; sepsis